PENGEMBANGAN MEDIA PEMBELAJARAN MENGGUNAKAN GAME EDUCAPLAY MENINGKATKAN KEMAMPUAN PEMECAHAN MASALAH MATEMATIKA KELAS VII SMP NEGERI 3 PADANGSIDIMPUAN - Ummi Fadilla; Eva Yanti Siregar; Sinar Depi Harahap (JURNAL MathEdu (Mathematic Education Journal), 2026)
This study aims to develop a learning medium using the Educaplay game to enhance the mathematical problem-solving skills of seventh-grade students at SMP Negeri 3 Padangsidimpuan. The study employs the ADDIE development model, which consists of five phases: analysis, design, development, implementation, and evaluation. The instruments used include validation sheets, practicality questionnaires, and problem-solving ability tests. The research subjects consisted of 23 students. Validity was determined based on assessments by three expert validators, each with expertise in the research variables. Practicality was assessed through student responses to the developed product via a questionnaire. Effectiveness was evaluated using student test scores.The analysis results show that the learning media using the Educaplay game for the topic of ratios achieved a validity percentage of 83.0%, categorized as very valid. The practicality reached 92.9%, categorized as very practical. The effectiveness was 100%, with more than 85% of students achieving mastery, indicating effective criteria. In conclusion, the development of the Educaplay learning media can enhance the mathematical problem-solving skills of seventh-grade students at SMP Negeri 3 Padangsidimpuan.